Pengembangan Gim Edukasi 2D Pengenalan Prosedur Keberangkatan Internasional di Bandara Soekarno-Hatta, Tangerang - Jimmy Dharmawan; Paramaresthi Windriyani (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to create a delivery medium in the form of a 2-dimensional educational game with the Android platform that can introduce simple procedures and a brief facilities for international departures at Soekarno-Hatta Airport in Tangerang. The method used for game development in this study is GDLC (Game Development Life Cycle). The GDLC method has 6 stages which consists of initiation that discusses the determination of game types and concepts, pre-production that discusses the prototype game, a production that discusses the development of the game, a trial that discusses the functional testing of the game, a beta that discusses testing by an external party, and a release. The results of this study are 2-dimensional educational games with APK file formats that can be run on Android smartphones.